Overview of tax measures for personal income tax of the period 2009-2020 - Koutroubi, Efstathia (International Conference on Business and Economics - Hellenic Open University, 2023)
The key components of fiscal policy for a fair and effective tax framework are the implementation of tax reform through a mixture of immediate measures to increase revenue. The Greek income tax system underwent important structural reforms. There was an urgent need to immediately increase the state budget revenues and in the framework of the rescue program of the Greek economy there was a series of legislative interventions. Measures were taken in 2012 to curb the downward trend in revenues, such as expansion of the tax base, reduction of tax exemptions, reduction of taxable income resulting from the restraint of public expenditure due to the adjustment of special payroll. Low levels of growth tend to be one of the main reasons for preventing the collection of personal income taxes. There is a negative correlation between the percentage of tax revenues from personal income taxes and economic growth. From 2020 major tax changes have been implemented with relief for employees, retirees, families with children, property owners. This study indicates that prerequisites for a successful tax reform include a holistic approach to the tax system, the evaluation and measurement of concrete reform proposals, as well as the possibility of achieving the objectives and choosing the appropriate timeframe for the adoption of the tax reform in connection with the economic crisis. Also, it provides the financial impact of measures for the taxation undertaken of personal income from 2009 to 2020. Keywords: Implementation of tax reform, personal income tax, expansion of the tax base, income redistribution JEL Classifications: H20, H21, H24, H29